2021
DOI: 10.1016/j.ejro.2021.100375
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of treatment response to transarterial radioembolization of liver metastases: Radiomics analysis of pre-treatment cone-beam CT: A proof of concept study

Abstract: To investigate the potential of texture analysis and machine learning to predict treatment response to transarterial radioembolization (TARE) on pre-interventional cone-beam computed tomography (CBCT) images in patients with liver metastases. Materials and Methods: In this IRB-approved retrospective single-center study 36 patients with a total of 104 liver metastases (56 % male, mean age 61.1 ± 13 years) underwent CBCT prior to TARE and follow-up imaging 6 months after therapy. Treatment response was evaluated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(5 citation statements)
references
References 32 publications
0
5
0
Order By: Relevance
“…The last and most diverse category we found eligible to compare was miscellaneous, including 29 journal article [ 6 , 8 , 9 , 33 , 50 , 52 , 56 , 71 , 161 , 164 , 173 179 , 181 – 184 , 186 188 , 191 , 194 , 195 , 205 , 206 ] and 8 proceeding paper [ 27 , 180 , 185 , 189 , 190 , 192 , 193 , 207 ] total thirty-seven studies. The aims of the studies are clinical-oriented.…”
Section: Resultsmentioning
confidence: 99%
“…The last and most diverse category we found eligible to compare was miscellaneous, including 29 journal article [ 6 , 8 , 9 , 33 , 50 , 52 , 56 , 71 , 161 , 164 , 173 179 , 181 – 184 , 186 188 , 191 , 194 , 195 , 205 , 206 ] and 8 proceeding paper [ 27 , 180 , 185 , 189 , 190 , 192 , 193 , 207 ] total thirty-seven studies. The aims of the studies are clinical-oriented.…”
Section: Resultsmentioning
confidence: 99%
“…Only some pilot studies have suggested radiomics features might be associated with outcome after TARE for HCC, liver metastases and intrahepatic cholangiocarcinoma. [89][90][91][92][93] Furthermore, good results were found for CT-radiomics predicting completeness of ablation in colorectal liver metastases, adrenal metastases and pulmonary malignancies. 94,95 In addition, Ma et al 96 used radiomics from contrast-enhanced ultrasound (CEUS) for prediction of recurrence in HCC lesions.…”
Section: Artificial Intelligence In Interventional Oncologymentioning
confidence: 99%
“…Transarterial radioembolization (TARE) has been investigated less extensively compared to TACE. Only some pilot studies have suggested radiomics features might be associated with outcome after TARE for HCC, liver metastases and intrahepatic cholangiocarcinoma 89–93 . Furthermore, good results were found for CT‐radiomics predicting completeness of ablation in colorectal liver metastases, adrenal metastases and pulmonary malignancies 94,95 .…”
Section: Artificial Intelligence In Interventional Oncologymentioning
confidence: 99%
“…Nevertheless, they did not observe significant additional prognostic value in these radiomics features for predicting overall survival when compared to information obtained solely from clinical parameters. Kobe et al [42] aimed to predict treatment response to TARE in patients with liver metastases using pre-treatment CT images, employing both traditional machine learning and deep learning algorithms. The model achieved an AUC of 0.850, a sensitivity of 94.2%, and a specificity of 67.7% in a testing set.…”
Section: Radiotherapymentioning
confidence: 99%